A Relational Database of Roman Law Based on Justinian's Digest. (5th August 2020) - Ribary, Marton
The Digest is the definitive historical sourcebook of Roman law compiled under the Byzantine emperor Justinian I (533 CE). This relational database includes the text of Theodor Mommsen's authoritative edition of the Digest with accompanying information about its compositional structure and its featured jurists. The data was collected from raw text files and transformed to structured machine-readable form in a Python coding environment. Preprocessed data stored in flat files were loaded to a single super lightweight SQLite database (<7Mb) which chains six tables to each other in many-to-one relationships. The database can be easily browsed, queried and expanded in a variety of free-to-use interfaces. Apart from reliable, efficient and structured information retrieval, the database assists large scale quantitative analyses and it can be used as the starting point for further computer-assisted Roman law projects.